2016
DOI: 10.2147/cmar.s90169
|View full text |Cite
|
Sign up to set email alerts
|

Role of tolvaptan in the management of hyponatremia in patients with lung and other cancers: current data and future perspectives

Abstract: Hyponatremia is the most frequently observed electrolyte abnormality in clinical practice, and its frequency is almost double in hospitalized cancer patients. As a subset of cancer, hyponatremia is quite common in lung cancer patients, and it is often coupled with the diagnosis of syndrome of inappropriate antidiuretic hormone secretion. The presence of hyponatremia is consequential in that its presence adversely affects cancer patients’ prognosis and outcomes. Limited data suggest that correcting hyponatremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 55 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…The relation between SIADH and ectopic ADH production by tumour cells has also been demonstrated in in vitro studies as high concentration of immune-reactive ADH has been found in tumour extracts of patients with SIADH (Thajudeen et al 2016). Northern blot and S 1 -nuclease analysis demonstrated the production of ADH mRNA in tumours and tumour cell lines from patients with SCLC and hyponatraemia.…”
Section: Syndrome Of Inappropriate Anti-diuretic Hormone Secretion (Smentioning
confidence: 75%
See 4 more Smart Citations
“…The relation between SIADH and ectopic ADH production by tumour cells has also been demonstrated in in vitro studies as high concentration of immune-reactive ADH has been found in tumour extracts of patients with SIADH (Thajudeen et al 2016). Northern blot and S 1 -nuclease analysis demonstrated the production of ADH mRNA in tumours and tumour cell lines from patients with SCLC and hyponatraemia.…”
Section: Syndrome Of Inappropriate Anti-diuretic Hormone Secretion (Smentioning
confidence: 75%
“…In contrast, the great majority of endocrine PNS produced from non-endocrine neoplasms are found in highly malignant tumours mainly involving the lungs, breasts, prostate, ovaries, skin, colon and certain forms of haematological malignancies; however, tumours arising from virtually any tissue have been implicated, albeit rarely (Lorch et al 2007, Nimalasena et al 2008, Gilmore et al 2009, Nella et al 2014, Dimitriadis et al 2015, Thajudeen et al 2016.…”
Section: Paraneoplastic Endocrine Syndromesmentioning
confidence: 99%
See 3 more Smart Citations